Analysis of Strength on Thick Plate Part using Genetic Algorithm Optimisation Method - S. M., Azlan; Z., Shayfull; S. M., Nasir; Mohd Sazli, Saad; Mohd Rashidi, Maarof; M., Fathullah (EDP Sciences, 2016)
This study focuses on the optimisation of the injection moulding parameters to maximise the strength ofmoulded parts using a simulation software. The moulded parts were injected with Acrylonitrile- Butadiene-Styrene (ABS) whereas mould temperature, melt temperature, packing pressure and packing time were selected as variable process parameters. The polynomial model obtained using Design of Experiment (DOE) was integrated with the Response Surface Methodology (RSM) and Centre Composite Design (CCD). The RSM was supported with Genetic Algorithm (GA) to anticipate the optimum value of processing parameters with the highest strength. It was found that strength of the parts can be improved 2.2% using the methodology reported herein.